Effective evaporation of CF4plasma modified PVDF membranes in direct contact membrane distillation - Yang, C.; Tian, M.; Xie, Y.; Li, X.; Zhao, B.; He, T.; Liu, Jian (Elsevier BV, 2015)
© 2015 Elsevier B.V. PVDF membranes, after surface modification by CF4plasma, have demonstrated surperhydrophobic surface characteristics and up to 30% flux enhancement in direct contact membrane distillation (MD). The heat transport in the MD process was modeled to assess the membrane distillation coefficients (Bm). The experimentally determined Bmshowed up to 50% deviation from the modeled values for CF4modified PVDF membranes. An effective evaporation factor, as a function of surface porosity and surface water contact angle, was proposed to correlate surface wettability contribution to the MD flux. This factor was fitted by comparing the experimentally determined flux with modeled one. It was found that the factor, which is positively related to surface water contact angle and surface porosity, varied with the membrane wettability and can rationally explain the deviation between observed and theoretical fluxes. In addition, CF4plasma modification could increase the membrane's evaporation efficiency from 54.3% for the virgin membrane up to 63.4% for surface modified membranes because of the increase of the effective evaporation area factor. The introduction of the factor provides a means to evaluate the membrane surface hydrophobicity to the MD flux and necessitate the development of super even ultra-hydrophobic membranes.